Beyond the Classroom: EFL Students’ Perceptions of Discord in Affecting Their Speaking Motivation - Pasaribu, Beta Rida; Adibah, Adibah; Sumarti, Siti (Journal Corner of Education, Linguistics, and Literature, 2025)
Discord has become a widely used platform for language learning interactions, yet students’ perceptions of its influence on their motivation to speak English remain underexplored. This study investigates how English as a foreign language (EFL) students perceive Discord’s influence on their motivation to engage in speaking practice. This study employed a case study design. Fifteen EFL high school students participated in this study, selected for their active use of Discord for English practice. Data were collected through a questionnaire and a semi-structured interview. The findings indicate that students generally feel more confident speaking English on Discord, and most are encouraged to continue improving their speaking skills on the platform. Students also show positive engagement, demonstrated by their interest in participating, willingness to communicate, and persistence even when making mistakes. However, Discord has not yet become their preferred environment for speaking activities, as some students still favor traditional or other interactive learning contexts. This study concludes that Discord positively affects students’ speaking motivation by providing a supportive, flexible communication space. These insights highlight the potential of integrating communication-based platforms into language learning practices to enhance students’ willingness to engage in speaking beyond the classroom.